Inhibiting UPF1 methylation enhances tumor immunotherapy sensitivity by reducing nonsense-mediated mRNA decay - Shengyu Zhu; Yucong Bai; Dongjing Zhang; Changsheng Huang; Xu Qian; Pengcheng Li; Tianci Xie; Qi Wu; Anyi Liu; Tong Zhu; Wangshuo Yang; Xiaowei She; et al. (Cell Reports, 2025)
Summary: Nonsense-mediated mRNA decay (NMD) is a conserved RNA surveillance mechanism. Inhibition of NMD leads to increased expression of tumor neoantigens encoded by genes with premature termination codons (PTCs), thereby enhancing tumor immunogenicity. In this study, we find that protein levels of up-frameshift protein 1 (UPF1), a key factor in the NMD pathway, show significant differences in clinical tumor samples of microsatellite-stable (MSS) and microsatellite-unstable (MSI) colorectal cancer (CRC). UPF1 protein levels negatively regulate tumor immunogenicity and sensitivity to anti-PD-1 therapy in MSS and MSI CRC mouse models. Mechanistically, asymmetric di-methylation of UPF1 R433 by protein arginine methyltransferase 4 inhibits the autophagic degradation of UPF1, and inhibiting UPF1 R433 methylation can weaken NMD, thus increasing the immunogenicity and anti-PD-1 sensitivity of CRC, regardless of MSS or MSI status. Our study highlights the potential of combination strategies in CRC immunotherapy, promising to expand the beneficiaries of immunotherapy and provide insights for new therapeutic targets.